2023
DOI: 10.1007/s10567-023-00437-4
|View full text |Cite
|
Sign up to set email alerts
|

What Do We Know About Depression Among Youth and How Can We Make Progress Toward Improved Understanding and Reducing Distress? A New Hope

Abstract: This paper summarizes many findings about depression among children and adolescents. Depression is prevalent, highly distressing, and exerts considerable burden worldwide. Rates surge from childhood through young adulthood and have increased over the last decade. Many risk factors have been identified, and evidence-based interventions exist targeting mostly individual-level changes via psychological or pharmacological means. At the same time, the field appears stuck and has not achieved considerable progress i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 174 publications
0
2
0
Order By: Relevance
“…However, it is di cult to estimate the long-term e cacy of psychotherapy. Despite the best efforts of researchers, the current interventions do not adequately satisfy the needs of adolescents with depression [52]. This may be the reason for the small therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is di cult to estimate the long-term e cacy of psychotherapy. Despite the best efforts of researchers, the current interventions do not adequately satisfy the needs of adolescents with depression [52]. This may be the reason for the small therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
“…The standardized mean difference (SMD) was -0.08 (95% CI: -0.20 to -0.03, p = 0.002, I 2 = 72%) and -0.12 (95% CI: -0.20 to -0.03, p = 0.01, I2 = 68%) at 1 and 2 years, respectively [ 63 ]. Despite the best efforts of researchers, the current interventions do not adequately satisfy the needs of adolescents with depression [ 64 ]. This may be the reason for the small therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Living with parents is a culture that exists in Indonesian society, and this condition is often found not only in young adults but also in children who already have families. The results of previous studies have shown that young adults living with their parents with closer relationships reported lower rates of depression (Romm et al, 2021); (Hankin & Griffith, 2023); (Idris & Tuzzahra, 2023). Living alone is more at risk of depression than living with a partner (Copp et al, 2018); (Honjo et al, 2018).…”
Section: Occupation Living Circumstances and Depressionmentioning
confidence: 98%